FROM DESIRE TO DESTRUCTION: HINDU ETHICS AS A MORAL CRITICISM OF THE FILM CONCRETE UTOPIA - Somawati, Ayu Veronika (UHN I Gusti Bagus Sugriwa Denpasar, 2026)
Humans, as social creatures (homo socius), cannot live alone and need interaction with other humans to live their lives well. To avoid friction between humans that can cause disorder, it is necessary to instill ethical values to maintain balance in social and personal life. One of the effective media to instill these ethical values is through movies, such as Concrete Utopia from South Korea. This study aims to use Hindu ethics as a moral critique of the film Concrete Utopia. This research uses a qualitative method with an analytical and descriptive approach. The researcher studied the movie Concrete Utopia as well as various literatures relevant to the focus of the problem. The data obtained were arranged systematically and analyzed to get a conclusion. The research results show that Concrete Utopia highlights the importance of ethical values in shaping human behavior and social interactions. Hindu ethics are used to critique several actions depicted in the film, including: the development of human desires, helping each other, courage, relationships that ideally should not be founded on lies, leadership, and human greed.